2013
DOI: 10.1038/psp.2013.32
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Simulation to Inform Phase 2: Comparison of Concentrated vs. Distributed First‐in‐Patient Study Designs in Psoriasis

Abstract: Clinical trial simulation (CTS) and model-based meta-analysis (MBMA) can increase our understanding of small, first-in-patient (FIP) trial design performance to inform Phase 2 decision making. In this work, we compared dose-ranging designs vs. designs testing only placebo and the maximum dose for early decision making in psoriasis. Based on MBMA of monoclonal antibodies in the psoriasis space, a threshold of greater than a 50 percentage point improvement over placebo effect at the highest feasible drug dose wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…To inform this modeling, a range of dose levels must be employed (as was done in the current study), in contrast to a single high‐dose level, proof‐of ‐concept approach. It has been shown that an equivalently sized study could provide dose–response information with negligible loss of proof‐of‐concept power by apportioning subjects with disease to a range of dose levels and employing model‐based analysis …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To inform this modeling, a range of dose levels must be employed (as was done in the current study), in contrast to a single high‐dose level, proof‐of ‐concept approach. It has been shown that an equivalently sized study could provide dose–response information with negligible loss of proof‐of‐concept power by apportioning subjects with disease to a range of dose levels and employing model‐based analysis …”
mentioning
confidence: 99%
“…It has been shown that an equivalently sized study could provide dose-response information with negligible loss of proof-of-concept power by apportioning subjects with disease to a range of dose levels and employing model-based analysis. 13 Semi-mechanistic pharmacokinetic-pharmacodynamic (PK-PD) models in psoriasis have been published for a few biologic compounds based on PASI score (treated as a continuous variable), 14,15 categorical scores such as PASI75, 16 the Physicians Global Assessment (a 6-point score) 17 and PASI component scores (as an improved way of modeling bounded outcome scores) 18 and inhibition of biomarkers CD11a 19 and CD4þ/CD8þ. 20 These examples were based primarily on Phase 3 data, and only the CD11a inhibition model 19 was based on Phase 1 data alone.…”
mentioning
confidence: 99%
“…In programs IIHV, the practice of including multiple active RN doses and performing dose ranging in the FIP trial may be explained by a wish to obtain dose–exposure–response information to inform anticipated clinical development. The go/no‐go decision‐making capability of FIP trials with a single or several active doses has been found to be comparable, the advantage of the latter being the obtainment of dose–exposure–response information to better inform forthcoming exploratory dose‐ranging trials . However, in the reviewed development programs, a large number of sponsors did not perform any post‐FIP exploratory trials, and hence a wish to accelerate clinical development by combining multiple objectives may also be a reason.…”
Section: Discussionmentioning
confidence: 99%
“…The go/no-go decision-making capability of FIP trials with a single or several active doses has been found to be comparable, the advantage of the latter being the obtainment of dose-exposure-response information to better inform forthcoming exploratory dose-ranging trials. 19 However, in the reviewed development programs, a large number of sponsors did not perform any post-FIP exploratory trials, and hence a wish to accelerate clinical development by combining multiple objectives may also be a reason. It has further been suggested that the rare occurrence of the confirming FIP trial in clinical development practice can indeed be attributed to time restraints in clinical development but also difficulty in objectively establishing proof of concept.…”
Section: Clinical Development Pathsmentioning
confidence: 99%
“…One of the most important aspects that must be taken into consideration is the construction of an accurate dose response relationship for both safety and efficacy to ensure the most appropriate dose range and/or ranges are taken further and tested in subsequent Phase III trials. Recent advances in the design of Phase II studies include application of computer tools to model and simulate clinical trials[42]. Modeling and simulation applied in Phase II are based on the availability of a biomarker linked either to the mechanism of action of the drug, or to a potential unwanted effect, or both.…”
Section: Introductionmentioning
confidence: 99%